Training for marathons during a marathon pandemic: effect of the COVID-19 pandemic on fitness among high-level nonelite runners - Matsumura, M. E.; Martin, B.; Matsumura, T.; Qureshi, A. (Journal of Sports Medicine, 2021)
Background. The COVID-19 pandemic has had a profound effect on all aspects of life, including physical fitness and well-being of the general population. In the present study, we assessed the effect of the pandemic on the subjective and objective fitness of high-level nonelite runners. Methods. The MASTERS Athletic Study is an ongoing survey of training and health habits of high-level nonelite runners, the majority of whom compete in marathons and other extreme endurance events. We invited participants to a web-based questionnaire regarding training and fitness during the COVID-19 pandemic. Comparisons were made between subjective and objective fitness as well as well as the relationship of prepandemic training volume and history of COVID-19 on change in fitness during the pandemic, using Mann-Whitney rank-sum tests and chi-square tests for nonparametric and categorical variables, respectively. Results. A total of 189 runners completed the survey, of whom 26 (13.8%) reported prior diagnosis with COVID-19. In terms of the subjective sense of fitness compared to before the pandemic, 49 (25.9%) reported they were less fit, 55 (29.1%) reported they were more fit, and 85 (45.0%) reported their fitness was unchanged. These assessments correlated well with objective measurement of training volume in MET-min/week. Runners with improved fitness at present had a lower calculated training volume before the pandemic versus those who reported unchanged or worsened fitness. There was no relationship between the report of prior COVID-19 and either subjective or objective measures of fitness. Conclusion. The COVID-19 pandemic has had a variable effect on the fitness of high-level nonelite runners. We found an inverse relationship between baseline training volume and the likelihood of runners reporting improved fitness and no relationship between a history of COVID-19 and change in fitness through the pandemic. Understanding the effect of the COVID-19 pandemic on athletic fitness will help guide strategies to maintain physical health and wellness through future public health crises.